Diversity and conservation of the large mammals from Loreto, Peru - Diaz, Silvia (2021)
In this work, we present an updated list of large mammals for Loreto composed of 72 species in 8 orders and 25 families. This list is elaborated from review of databases, zoological collections, and scientific publications. In Loreto is registered five Peruvian endemic species: Lagothrix flavicauda, Saguinus (Leontocebus) illigeri, Saguinus (Leontocebus) nigrifrons, Pithecia aequatorialis and Pithecia isabela; the last three have presence only in Loreto. We found 292 different locations and 3286 records of large mammals and build a distribution map highlighting ecoregions and historical (before 2001) and contemporary (after 2001) records. Likewise, we build maps for each of the 72 species with records in Loreto, and a density map that reveal two areas with information gaps: 1) the Datem del Marañón-Loreto zone, and 2) the Alto Amazonas-Ucayali zone. These zones require urgent evaluations to complement knowledge of Loreto's biodiversity and adequately support conservation and sustainable development plans.